Strengthening proposal and anal ytical simulation of the pseudo-dynamic test-response of a full-scale rc infilled model of an existing rc structure - Chrysostomou, Christis; Kyriakides, Nicholas; Poljanšek, Martin; Taucer, Fabio (My University, 2013)
The effectiveness of seismic retrofitting of multi-storey multi-bay RC-frame buildings by converting selected bays into new walls through infilling with reinforced concrete (RC) was studied experimentally at the ELSA facility of the Joint Research Centre in Ispra (Italy). A full-scale model was tested with the pseudo-dynamic method and consisted of two four-storey (12m tall) three-bay (8.5m long) parallel frames linked through 0.15m slabs with the central bay (2.5m) infilled with a RC wall. The frames were designed and detailed for gravity loads only and are typical of similar frames built in Cyprus in the 1970's. Different connection details and reinforcement percentages for the two infilled frames were used in order to study their effects in determining structural response. The results of the pseudo-dynamic and cyclic tests performed on the specimen and their analytical simulation are presented, and conclusions are drawn.
Keywords: Full-scale pseudo-dynamic testing; RC infill walls; Retrofitting existing structures